Effects of country debt risk and determinant indicators on volatility contagion in six selected Asian countries - Lee, See Nie (2016)
Volatility contagion has become a trend of financial crisis research ever since the outbreak of 2007 Sub-prime crisis in the US. Existing contagion studies are either too sector based, or focus on specific financial product so there is a lack of comprehensive study to incorporate multiple indicators driving the volatility contagion. This study analysed multiple sources that can be associated with volatility contagion, comprising both the financial and non-financial sectors, market information, macroeconomic financial variables, country debt risks and external factors (S&P 500) combined together as variety types of indicators driving the volatility contagion. A generalised VAR-GARCH with multivariate BEKK-GARCH approach is employed to analyse volatility contagion of daily sectorial indices of six Asian countries (Indonesia, Japan, Malaysia, South Korea, Thailand and the Philippines from 1990 until 2015. When AIC criterion information was analysed, it showed that the VAR(1)-GARCH(1,1) model benchmark was robust. This covers four financial crisis: Savings and Loan Crisis (early 1990s), Asian Financial Crisis (1997), the Internet Bubble Bursting (2002) and the Sub-prime Mortgage Crisis (2007). The research design is partitioned into three stages. The first stage is analyse the structure of volatility contagion within the selected six Asia countries and US. The start of financial crisis, strong interconnection exists between bank credit risk and sovereign credit risk. And, a high country debt risk will lead to instability economy in a country and then slip into a contagion circumstances. However, there is lack of literature provide empirical evidence of the country debt risk on volatility contagion. Hence, in the second stage, this study measure country debt risk to explore whether the volatility contagion is driven by country debt risk fluctuation. And lastly is testing the main objective. Although many of the previous research investigated indicators of volatility contagion, but there is still a lack of comprehensive investigation on the combination of variety types of indicators. After filtering down the possible indicators of volatility contagion, this study identify the fourteen major indicators from different sectors driving the volatility contagion, country debt risk is one of them. The results documented statistical evidence at highly significant of volatility contagion during all the selected four financial crisis, except for South Korea and the Philippines, no volatility contagion was shown between these two countries during the period of Savings and Loan Crisis. This study further explore on a determinant of volatility contagion that receive rare attention in the literature - country debt risk with a Two-limit Tobit model. This study proxy it by debt service capacity which is measured by quarterly-ahead debt restructuring ratios. The result reveals that the country debt risk had increased for all the countries during and after six financial crisis and it is one of the important indicators driving volatility contagion. Furthermore, our findings revealed that the volatility contagion was not caused by a single factor. Rather, all volatility contagion have multiple indicators. This is contrary to previous studies which focused only on specific sectors or products.